ROR1 is Expressed in Diffuse Large B-Cell Lymphoma (DLBCL) and a Small Molecule Inhibitor of ROR1 (KAN0441571C) Induced Apoptosis of Lymphoma Cells - Amineh Ghaderi; Amir Hossein Daneshmanesh; Ali Moshfegh; Parviz Kokhaei; Jan Vågberg; Johan Schultz; Thomas Olin; Sara Harrysson; Karin E Smedby; Elias Drakos; Georgios Z. Rassidakis; Anders Österborg; et al. (Biomedicines, 2020)
The receptor tyrosine kinase ROR1 is absent in most normal adult tissues, but overexpressed in several malignancies. In this study, we explored clinical and functional inhibitory aspects of ROR1 in diffuse large B-cell lymphoma (DLBCL). ROR1 expression in tumor cells was more often observed in primary refractory DLBCL, Richter’s syndrome and transformed follicular lymphoma than in relapsed and non-relapsed DLBCL patients (p < 0.001). A survival effect of ROR1 expression was preliminarily observed in relapsed/refractory patients independent of gender and stage but not of age, cell of origin and international prognostic index. A second generation small molecule ROR1 inhibitor (KAN0441571C) induced apoptosis of ROR1+ DLBCL cell lines, similar to venetoclax (BCL-2 inhibitor) but superior to ibrutinib (BTK inhibitor). The combination of KAN0441571C and venetoclax at EC50 concentrations induced almost complete killing of DLBCL cell lines. Apoptosis was accompanied by the downregulation of BCL-2 and MCL-1 and confirmed by the cleavage of PARP and caspases 3, 8, 9. PI3Kδ/AKT/mTOR (non-canonical Wnt pathway) as well as β-catenin and CK1δ (canonical pathway) were inactivated. In zebra fishes transplanted with a ROR1+ DLBCL cell line, KAN0441571C induced a significant tumor reduction. New drugs with mechanisms of action other than those available for DLBCL are warranted. ROR1 inhibitors might represent a novel promising approach.